Progressive Stroke Caused by Neurosyphilis With Concentric Enhancement in the Internal Cerebral Artery on High-Resolution Magnetic Resonance Imaging: A Case Report - Zhang, Kejia; Chu, Fengna; Wang, Chao; Shi, Mingchao; Yang, Yi (Frontiers in Neurology, 2021)
Background: Neurosyphilis can initially present as a stroke. However, the general management strategy for stroke may not be effective for this condition. Intracranial vessel wall imaging indicating arteritis can help differentiate neurosyphilis from other causes of stroke. Case presentation: A 59-year-old Chinese woman with an acute infarct in the left basal ganglia and multiple stenoses in the bilateral middle cerebral arteries, anterior cerebral artery, and basilar artery, aggravated twice, despite antiplatelet treatment. High-resolution magnetic resonance imaging (HR-MRI) suggested concentric enhancement in the left middle cerebral artery. Treponema pallidum test results were positive, suggesting neurosyphilis. Conclusions: HR-MRI provides valuable information regarding arteritis, which is helpful in differentiating neurosyphilis from other causes of stroke. Antiplatelet medication should be used judiciously for neurosyphilis-related stroke.